Deep Cross-Cultural Reconstruction Process in the Context of Cultural Potential: A Qualitative Study - Zhang, Fengyi; Xie, Jinyu; Luo, Ling (Frontiers in Psychology, 2022)
Cross-cultural adaptation significantly impacts the development of individuals in different cultural environments. Because of culture and art scholars’ intense cultural intervention, their cross-cultural process—cultural reconstruction—significantly differs from that of other groups. However, there is insufficient research on them. In this study, 29 contemporary Chinese artists living in Germany were interviewed. Grounded theory was used to propose a new ladder theory. We found that the cross-cultural reconstruction process includes two sub-processes and seven ladder-like stages containing the “driver-strategy-outcome” logic. Arguably, the ladder model provides a stronger explanation for the interface between culture and art scholars’ cross-cultural reconstruction process.